Injúria renal aguda em unidade de terapia intensiva: um estudo longitudinal - Santos, Reginaldo Passoni dos (2018)
The objective of this study was to identify the occurrence and risk factors for Acute Kidney Injury (AKI) in critically ill Brazilian patients. Study retrospective, documentary and with quantitative approach. The AKI identification was performed using the criteria proposed by the acronym KDIGO (Kidney Disease Improving Global Outcomes). Data were collected, between October 2016 and January 2018, from patients admitted to the Intensive Care Unit (ICU) between January 2011 and December 2016 Was used a form constructed and validated specifically for use in the study, which extracted patients' information registered at admission to the ICU, which refer to the clinical- epidemiology patients profile, as well as laboratory and hemodynamic parameters and the need for dialysis. The data collected evaluated the AKI incidence, its risk factors and the overall mortality rate, as well as among AKI patients and among patients with dialysis. Descriptive and inferential statistical analyzes were performed, using logistic regression tests and the receiver operating characteristic (ROC) curve. In all analyzes p-value <0.05 was considered statistically significant and all data were analyzed in software R. The study included 1,500 patients, AKI incidence was 40.5% (n = 608) and need of dialysis was 13% (n = 79). The risk factors at ICU admission to AKI occurrence were: hypertension (odds ratio (OR) = 1.44, 95% confidence interval (CI) = 1.07-1.94, p = 0.017), serum creatinine concentration (OR = 3.54; 95% CI = 2.65-4.73; cutoff: >1.16 mg/dL; p <0.001), serum albumin concentration (OR = 1.42, 95% CI = 1.07-1.89, cutoff: 0.35, p 0.015), APACHE II score (OR = 2.10, 95% CI = 1.56-2.81, cutoff: >24 points, p <0.001) and SAPS 3 score (OR = 1.75, 95% CI = 1.31-2.33, cutoff: >68 points, p <0.001). The overall mortality rate was 18.5%, at AKI patients 39.1%, and at patients with AKI dialytic 62%. The AKI incidence was high and the data are consonant with the literature. We identified the AKI predictors among critically ill Brazilian patients, and the results of this study may contribute to the implementation of targeted care therapies, as well as to establish strategies that can promote patient safety.